2007
DOI: 10.1242/jeb.010025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoperiod history on body mass and energy metabolism in Brandt's voles (Lasiopodomys brandtii)

Abstract: SUMMARY Many small mammals respond to seasonal changes in photoperiod via alterations in morphology, physiology and behaviour. In the present study, we tested the hypothesis that the preweaning (from embryo to weaning) photoperiod experience can affect subsequent development in terms of body mass and thermogenesis. Brandt's voles (Lasiopodomys brandtii) were gestated and reared to weaning under either a short (SD, 8 h:16 h L:D) or a long photoperiod (LD, 16 h:8 h L:D) at a constant ambient tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 58 publications
0
3
0
1
Order By: Relevance
“…The present data also showed that weight gain became higher in long-day A. chevrieri than short-day A. chevrieri. Lu et al (2007) found that Brandt's voles experiencing short-day history increased their body mass and body fat mass after being transferred to the long-day condition, suggesting that not only short day but also long day imposed a great effect on body mass. It was reported that the species showing decreases in body mass or body fat mass in fall for seasonal acclimatization or short day for acclimation tended to resist to high-fat diet-induced obesity (Peacock & Speakman 2001;Krol et al 2005).…”
Section: Body Mass and Body Compositionsmentioning
confidence: 94%
“…The present data also showed that weight gain became higher in long-day A. chevrieri than short-day A. chevrieri. Lu et al (2007) found that Brandt's voles experiencing short-day history increased their body mass and body fat mass after being transferred to the long-day condition, suggesting that not only short day but also long day imposed a great effect on body mass. It was reported that the species showing decreases in body mass or body fat mass in fall for seasonal acclimatization or short day for acclimation tended to resist to high-fat diet-induced obesity (Peacock & Speakman 2001;Krol et al 2005).…”
Section: Body Mass and Body Compositionsmentioning
confidence: 94%
“…The animals were in the chambers without bedding for about 60 min to stabilize and each test lasted for 60 min with oxygen consumption recordings at 5 min intervals. The two lowest consecutive readings were used to calculate RMR and corrected to standard temperature and pressure (STP) conditions (Lu et al, 2007). Body mass (BM) of voles was measured before and after each test.…”
Section: Resting Metabolic Ratesmentioning
confidence: 99%
“…This can change cognition, mentality, psychology and behavior (Lucas 2005;Plagemann 2005). Field and laboratory studies have shown that different environmental experiences, such as photoperiod (Lu et al 2007), temperature (Zhang et al 2011), alimentary effect (Lou et al 2015), social effects (Mirescu et al 2004;Lieberwirth et al 2012) and stress (Fan et al 2009;Storm & Lima 2010;Toumi et al 2016) significantly affect maternal reproductive strategies during the breeding season, and have a long-term effect on the growth and metabolic phenotype of offspring.…”
Section: Introductionmentioning
confidence: 99%